Polytopic vaccination with a live-attenuated dengue vaccine enhances B-cell and T-cell activation, but not neutralizing antibodies. Issue 3 (March 2017) - Hunsawong, Taweewun; Wichit, Sineewanlaya; Phonpakobsin, Thipwipha; Poolpanichupatam, Yongyuth; Klungthong, Chonticha; Latthiwongsakorn, Napaporn; Thaisomboonsuk, Butsaya; Im-erbsin, Rawiwan; Yoon, In-Kyu; Ellison, Damon W.; Macareo, Louis R.; Srikiatkhachorn, Anon; et al.
Abstract: Dengue, caused by dengue viruses (DENVs), is the most common arboviral disease of humans. Several dengue vaccine candidates are at different stages of clinical development and one has been licensed. Inoculation with live-attenuated DENV constructs is an approach that has been used by vaccine developers. Unfortunately, the simultaneous injection of all four attenuated DENV serotypes (DENV1-4) into a single injection site (monotopic vaccination) has been postulated to result in interference in the replication of some serotypes in favor of others, an important obstacle in obtaining a balanced immune response against all serotypes. Here, we demonstrate the virus replicative and immunostimulatory effects of polytopic monovalent dengue vaccination (PV) in which, each of the four components of the tetravalent vaccine is simultaneously delivered to four different sites versus the more traditional monotopic tetravalent vaccination (MV) in a non-human primate (NHP) model. With the exception of DENV-2, there was no significant difference in detectable viral RNA levels between PV and MV inoculation. Interestingly, longer periods of detection and higher viral RNA levels were seen in the lymph nodes of NHPs inoculated PV compared to MV. Induction of lymph node dendritic cell maturation and of blood T- and B-cell activation showed different kinetics in PV inoculated NHPs compared to MV. The MV inoculated group showed earlier maturation of dendritic cells and activation of B and T cells compared to PV inoculated NHPs. A similar kinetic difference was also observed in the cytokine response: MV induced earlier cytokine responses compared to PV. However, similar levels of DENV neutralizing antibodies were observed in PV and MV NHPs. These findings indicate that cellular immune response after vaccination may be affected by the location of inoculation. Design of vaccine delivery may need to take into account the effects of locations of vaccine delivery of multiples serotype live viral vaccine on the induction of immune response.